Manufacture of parquet flooring from rubberwood - Zafar Z (In: Proceedings of the International Rubberwood Seminar, 21-22 May 1990, Kuala Lumpur, Malaysia, pp.51-54., 1990)
The paper discuss with the feasibility of rubber wood for the manufacture of parquet flooring. The production procedure for the manufacture of three layer panel-type of parquet is described in the paper. The main advantage of this industry is it only requires very small sized timber (0.25 X 0.90 X 4.5 inch) thereby the wastes and off-cuts of furniture industry and other rubber wood industry, wood with defects such as knots wanes, pin-holes and several other defects can very efficiently used for paraquet flooring applications.
Keywords: Rubberwood; Rubberwood flooring